Reputation Management: A Critical Analysis of Media Representation and Community Perceptions in Amahlathi Local Municipality, South Africa - Qaba, Pikolomzi; Dlamini, Bongani I (New Advances in Business, Management and Economics Vol. 5, 2025)
The management of reputation has become a critical concern for local governments globally, as a positive reputation is essential for maintaining public trust, attracting investment, and ensuring effective governance. In South Africa, local governments face unique challenges in managing their reputation, given the country's complex socio-political landscape and historical legacies. This study examines the dynamic relationship between media representation and community perceptions in shaping the reputation of local government. Focusing on Amahlathi Local Municipality in South Africa, this research investigates how media reports reflect the opinions and experiences of community members, influencing the municipality's reputation. Using a qualitative content analysis approach, this study analyzed community feedback to identify patterns and themes in media representation. Underpinned by the Stakeholder Theory, Reputation Management Frameworks, and Social Exchange Theory. The study has implications for proactive reputation management, community engagement, transparency, and collaborative media relations. The findings suggest that media reports often prioritize negative narratives, perpetuating a negative reputation of the municipality. Conversely, community members expressed concerns about service delivery, accountability, and transparency. The study concluded the significance of stakeholder engagement, transparency, accountability, and performance in shaping ALM's reputation. By prioritizing stakeholder engagement, transparency, accountability, and performance, municipalities can enhance their reputation, improve governance, and deliver effective services to communities. The study contributes to the existing literature on reputation management in local government, highlighting the significance of media-community dynamics in shaping municipal reputation. The research underscores the need for proactive reputation management strategies, emphasizing community engagement, transparency, and collaborative media relations.